Stationary Lead-Acid Batteries : General Requirements And Methods Of Test Part 1. Vented Types BSI 1992 (BSI, 1992)
Electric cells, Electrical engineering, Lead-acid batteries, Storage batteries, Stationary, Ratings, Performance, Life (durability), Testing conditions, Specimen preparation, Electrical testing, Performance testing, Endurance testing, Short-circuit current tests, Test equipment, Circuits, Accuracy